Procedural outcome and risk prediction in patients with implantable cardioverter-defibrillator (ICD) undergoing transvenous lead extraction: a GALLERY subgroup analysis. (19th May 2022) - Chung, D; Burger, H; Kaiser, L; Osswald, B; Baersch, V; Naegele, H; Knaut, M; Reichenspurner, H; Willems, S; Butter, C; Pecha, S; Hakmi, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Device complications, such as infection or lead dysfunction necessitating transvenous lead extraction (TLE) are continuously rising amongst patients with indwelling transvenous implantable cardioverter-defibrillator (ICD). Objectives: Aim of this study was to characterize the procedural outcome and risk factors of patients with indwelling 1- and 2-chamber ICD undergoing TLE. Methods: We conducted a subgroup analysis of all 1- and 2-chamber ICD patients in the GALLERY (GermAn Laser Lead Extraction RegistrY) database. Predictors for procedural failure and all-cause mortality were assessed. Results: A total of 854 patients with ICD undergoing TLE were identified, who were younger (62.9±13.8 vs. 70.7±13.0 years; p<0.001), less likely to be female (20.8 vs. 27.1%; p<0.001) and had a higher proportion of patients with coronary artery disease (51.5 vs. 38.6%; p<0.001) and highly reduced ejection fraction (32.0 vs. 23.0%; p>0.001), when compared to non-ICD patients. Leading extraction indication was lead dysfunction (48.0 vs. 21.9%; p<0.001), followed by device-related infection (45.6 vs. 73.0%; p<0.001). There were no differences in overall procedural complications (4.3 vs. 4.3%; p=0.980), clinical success rate (97.9 vs. 97.8%; p=0.861) or procedure-related (0.8 vs. 0.5%; p=0.292) and all-cause mortality (3.4 vs. 3.7%; 0.742) between groups. Multivariate analysis revealed lead age≥10 years (OR:5.75, 95%CI:2.0-16.2; p=0.001) as independent predictor for procedural failure. Systemic infection as extraction indication (OR:9.57, 95%CI:2.2-42.4; p=0.003) and procedural complications (OR:8.0, 95%CI:2.8-23.3; p<0.001) were identified as risk factors for all-cause mortality. Predictors for systemic infection in ICD patients were atrial fibrillation (OR: 2.22, 95%CI: 1.51-3.27; p<0.001), diabetes mellitus (OR: 2.28, 95%CI: 1.59-3.25; p<0.001) and chronic kidney disease (OR: 2.0, 95%CI: 1.39-2.89; p<0.001). Conclusions: Transvenous lead extraction is safe and efficacious in patients with 1- and 2-chamber ICD. Although lead dysfunction is the leading indication for extraction, systemic device-related infection is the main driver of all-cause mortality for ICD patients undergoing TLE.